UPAYA PENYELESAIAN WANPRESTASI ATAS PINJAMAN KREDIT DENGAN JAMINAN SK PNS (STUDI PADA BANK MANDIRI KCP MEDAN WAHIDIN) - Siallagan, Praja Yudha Balista; Kaban, Maria; Sembiring, Idha Aprilyana (Sriwijaya Journal of Private Law, 2024)
Abstract  : One form of credit provided to civil servants (PNS) is the Fixed Income Credit Group (KRETAP). The Civil Servant Certificate (SK PNS) can be used as collateral for bank loans, as it is considered an acceptable form of security by several banks. However, the process of granting credit loan facilities can encounter obstacles, one of which is the borrower's default in paying installments. Therefore, this thesis is entitled "Efforts to Resolve Default on Credit Loans Secured by Civil Servant Certificates (Study at Bank Mandiri KCP Medan Wahidin)." The research questions in this thesis are: How is the regulation of credit loans with SK PNS collateral at Bank Mandiri KCP Medan Wahidin, what forms of default are committed by civil servants in credit loans with SK PNS collateral, and what efforts are made by Bank Mandiri KCP Medan Wahidin to resolve default disputes on credit loans with SK PNS collateral. The research method used in writing this thesis is the normative juridical research method, which refers to legal norms conducted through library research to obtain secondary data in the form of primary, secondary, and tertiary legal materials, and this research is descriptive in nature. Data collection techniques include library research and interviews with Bank Mandiri KCP Wahidin officials. The results obtained from this legal research show that the regulations of Bank Mandiri KCP Medan Wahidin in granting credit loans to civil servants (PNS) with Civil Servant Certificates (SK PNS) as collateral have a structured and meticulous process. The process begins with the collection of required documents, such as a copy of the SK PNS, identity card, salary slip, and other documents according to the bank's policy. The forms of default committed by civil servants in credit loans with SK PNS collateral include the borrower being transferred or reassigned during the credit repayment process, resulting in the borrower failing to meet obligations; the borrower being honorably or dishonorably discharged during the credit repayment process; and the borrower passing away during the credit repayment process. The efforts made by Bank Mandiri KCP Medan Wahidin to resolve default disputes on credit loans with SK PNS collateral involve fair and mutually beneficial negotiations, offering options for rescheduling, restructuring, or credit restructuring for borrowers facing payment difficulties. Keywords : Credit, SK PNS, Default.